Clinical characteristics, treatment intent, and outcome in a consecutive 10-year cohort of oral cancer patients aged 75 years and older. Issue 3 (April 2021) - Chieng, CY.; Davies, A.; Lowe, D.; Bekiroglu, F.; Khattak, O.; Schache, A.; Shaw, R.; Rogers, S.N.
Abstract: The prevalence of oral squamous cell carcinoma (OSCC) in the elderly is expected to increase by nearly a third in the next decade. Its management in older patients is potentially more challenging due to their pre-existing medical comorbidities, frailty, reduced life expectancy, and social issues. The aim of this retrospective review was to report on treatment given to patients aged 75 years and over, case mix, and survival. All patients aged 75 years and over who were diagnosed with OSCC in Merseyside between 1 January 2007 and 31 December 2016, and treated with either curative or palliative intent, were included. Their hospital notes were reviewed. Fisher's exact test and Kaplan-Meier analysis were used for data analysis. There were 236 patients (median (IQR) age 81 (78-86) years); 67% were treated curatively and 33% palliatively. Factors associated with palliation included older age, advanced tumour stage, cognitive impairment, and residence in a nursing or residential home. Of the 165 patients who were offered curative treatment, six (4%) declined due to personal or family reasons. Overall survival for palliative patients was 12% at one year and 7% at two years, whereas for patients treated curatively it was 74% at one year, 56% at two years, and 34% at five years. Patients over 85 years of age were less likely to have composite free flaps and postoperative radiotherapy. Perioperative mortality was 2.6%. Improvements in surgical techniques and perioperative management have enabled clinicians to offer treatment with curative intent to older frail patients, and with careful case selection outcomes can be very good.